1997
DOI: 10.1002/(sici)1520-6629(199709)25:5<421::aid-jcop4>3.3.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

The influence of an Africentric worldview and demographic variables on drug knowledge, attitudes, and use among African American youth

Abstract: s Alcohol, tobacco, and other drug use are major problems in the inner cities, especially for African American youth. Africentric values may be a protective factor for negative drug outcomes. The purpose of this study was to examine the influence of Africentric values, spirituality, and demographic variables on drug knowledge, attitudes, and use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(91 citation statements)
references
References 4 publications
3
86
2
Order By: Relevance
“…Regarding family structure, having two adults in a household (compared to single-parent households) may lead to more supervision and monitoring and subsequently less drug use (Amey & Albrecht, 1998;Belgrave et al, 1997). At the same time, high family conflict among parents and parental tobacco and alcohol use behaviors are predictive of lower refusal efficacy and substance use among youths (Bray et al, 2001).…”
Section: Family Factorscontrasting
confidence: 99%
See 1 more Smart Citation
“…Regarding family structure, having two adults in a household (compared to single-parent households) may lead to more supervision and monitoring and subsequently less drug use (Amey & Albrecht, 1998;Belgrave et al, 1997). At the same time, high family conflict among parents and parental tobacco and alcohol use behaviors are predictive of lower refusal efficacy and substance use among youths (Bray et al, 2001).…”
Section: Family Factorscontrasting
confidence: 99%
“…Drug refusal efficacy-defined as one's ability to not use drugs when involved in situations in which one is pressured by peers or colleagues to use drugs (Botvin & Kantor, 2000)-is a principal factor in determining adolescent drug and alcohol use expectations and behaviors (Belgrave et al, 2004). Several studies have shown that African-American adolescents and young adults who report higher levels of self-efficacy engage in less risky behaviors, including sexual risk behaviors and drug and alcohol use (Belgrave, Townsend, Cherry, & Cunningham, 1997;Jemmott, Jemmott, Fong, & McCaffree, 1999). Moreover, prevention programs based on increasing drug refusal efficacy have shown reductions in substance use and associated behaviors (Belgrave et al, 2004;Griffin, Botvin, Nichols, & Doyle, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Cultural values and beliefs such as communalism, spirituality, importance of kinship relations, collectivism, unity, cooperation, and awareness of racial disparities in mainstream culture are central themes in the socialization of African American children (Constantine, Gainor, Ahluwalia, & Berkel, 2003;Utsey, Adams, & Bolden, 2000). Communalism, defined as a belief in the importance of group over the individual and cooperation rather than competition (Belgrave, Townsend, Cherry, & Cunningham, 1997), indicates that the self is seen as a part of the collective whole. The emphasis on collectiveness and group harmony is reflected in the African philosophy ''I am because we are and since we are, therefore I am'' (Mbiti, 1969, p.152).…”
Section: African American Familiesmentioning
confidence: 99%
“…The use of culturally specific principles with African-Americans has been the focus of research (e.g. Beckett, Dungee-Anderson, Cox, & Daly, 1997;Belgrave, Townsend, Cherry, & Cunningham, 1997;Swigonski, 1996). It appears that embracing principles that are primarily African based, rather than European based, has a positive impact on social functioning (Jaegars, 1996).…”
Section: Strategy 5: Seek Culturally Appropriate and Successful Intermentioning
confidence: 99%